Spin-One DKP Equation in the Presence of Coulomb and Harmonic Oscillator Interactions in (1 + 3)-Dimension - H. Hassanabadi; Z. Molaee; M. Ghominejad; S. Zarrinkamar (Advances in High Energy Physics)
In this work, we study Duffin-Kemmer-Petiau equation in the presence of coulomb and harmonic oscillator potentials in (1+3)-dimension for spin-one particles and we obtain energy eigenvalues and corresponding eigenfunctions.